Workaholism among nurses in China: a nationwide cross-sectional survey - Yan Gao; Hongmin Ye; Shuqin Hong; Xue Bai; Xiuni Gan (BMC Nursing)
Abstract Background Anxiety and depression among nursing staff, stemming from difficulties in balancing high-pressure, high-load work with daily life, are on the rise. This phenomenon may be linked to workaholism among clinical nurses, yet the prevalence of workaholism among Chinese nurses remains underreported. Objectives To investigate the current state of workaholism among Chinese nurses and identify factors influencing it. Methods We distributed study information and a survey link via WeChat to professional nursing networks. The survey included demographic characteristics and the Dutch Work Addiction Scale (DUWAS). Descriptive and comparative analyses were performed, and multiple regression analysis was performed using the workaholism score as the dependent variable. Results A total of 3,596 Chinese registered nurses participated in the survey. The mean workaholism total score was 29.87 (SD = 4.93), with an average item score of 2.99 (SD = 0.49). Regression analysis revealed that education level (β=0.05), position (β=0.11), professional title (β=0.10), weekly night shifts (β=0.07), and weekly work hours (β=0.15) were positively associated with workaholism. Additionally, compared to nurses without children, those with children (β=0.06) exhibited higher levels of workaholism (all P < 0.05). Conclusions Chinese nurses exhibit moderate levels of workaholism. Nursing managers can enhance occupational well-being and reduce workaholism by implementing targeted interventions focused on key factors such as educational background, professional title, position, weekly night shift frequency, average weekly working hours, and parental status. Clinical trial number Not applicable.